Greyness Is Aged, Bearded Is Adult: Yoruba Age and Seniority - Agwuele, Augustine (Nordic journal of African studies, 2024)
I explore how Yoruba people ascertain who is junior, who is senior, and the mark of equality beyond obvious age, as well as the social function of these distinctions in everyday life. The social ranking of people as either senior, junior or mate is an invaluable principle of social organization among the Yoruba. It features prominently in determining privileges and access, and in orchestrating interpersonal relationships and modes of interaction. I examine linguistic and non-verbal signs drawn from popular cultural performances, habitual practices and proverbs, including sozialised roles and habitual typification which representing the cogitations of a Yoruba senior, to provide an ethnographic description of this social practice in its historical and contemporary form. In addition to the linguistic evidence, the opinions of subjects interviewed on the subject are presented. Taken together, the various sources of information show that this classification system operates within integrated cultural institutions that rest on their origination precepts, goals of earthly existence, and sociation habitudes. The system and its utility persist as they are fundamentally woven into the psychology of the children during their formative years within the lineage, and into the worldview of others through enculturation since people's life chances are partly dependent on their position within their nuclear family and their lineage.